Management of intercondylar femur fracture with distal femur locking compression plate: outcome analysis of 72 cases - Khan, Nadeem Ashraf; Atif, A. M.; Chatterjee, Abhinandan (International Journal of Research in Orthopaedics, 2020)
Background: Supra-condylar and inter-condylar fractures of the distal femur account for 7% of all femoral fractures and have always been difficult to treat and regaining full knee function is often difficult. The purpose of this study is to evaluate the functional outcome, fracture healing, complications of distal femoral intercondylar fractures managed by locking compression plate. Methods: Total 72 patients of intercondylar femur fracture were operated by ORIF with distal femur-locking compression plate via the standard swashbuckler approach. The functional outcomes were analyzed using modified hospital for special surgery scoring system. Results: Muller type C2 fracture was the most common fracture type with 50 out of 72 patients. The average range of motion achieved was about 99.03°±24.73° (Closed fractures =105.83°±19.41°and open fractures = 89.50°±28.36°). There was also a significant difference in the duration of operative time, 84.28±18.32 minutes for closed fractures and 98.46±22.47 minutes for open fractures. The average duration for radiological union was 14.52±2.21 weeks for closed and 17.20±2.44 weeks for open fractures. The average knee score was 80.13±13.38 using modified Hospital for Special Surgery score. Conclusions: Closed fractures have a higher range of motion and a better knee score compared to open fractures, supporting the fact that soft tissue compromise also affects range of motion and post-op rehabilitation of the limb. The outcome seems to correlate with the nature of injury i.e. high vs low velocity, type of fracture, anatomic reduction, associated injuries, time elapsed since injury to fixation and the stability of fixation.